Behavioural Time Allocation in Suckled Buffaloes: Analysis of Pre- and Post-Estrus Periods (Indian Journal of Animal Production and Management, 2024)
This study aims to investigate time spent on  eating, rumination, and resting during the three  days before, the day of, and three days after, estrus  in suckled buffaloes. Two experiments were  conducted with 24 buffaloes each. In Experiment 1,  buffaloes were divided into three groups (n=8): NC  (No Cow-Calf and Cow-Bull Contact), RC  (Restricted Cow-Calf and Fenceline Cow-Bull  Contact), and FC (Fenceline Cow-Calf and Cow Bull Contact). In Experiment 2 (n=12), buffaloes  were divided into two groups: RC (Restricted Cow Calf and No Cow-Bull Contact) and FC (Fenceline  Cow-Calf and Direct Cow-Bull Contact). The data  on mean frequencies of the time spent on eating,  rumination and resting behaviours were compared  between treatments on 3 days before oestrus (d -3,  -2, -1), the day of oestrus (d 0) and 3 days after  oestrus (d +1, +2, +3), using Duncan’s Multiple  Range test and a one-way ANOVA. There was a  significant effect of time (P
Keywords: bull biostimulation; direct contact; fenceline contact; estrous; time budget